Networked Systems : Third International Conference, NETYS 2015, Agadir, Morocco, May 13-15, 2015, Revised Selected Papers - Bouajjani, Ahmed; Fauconnier, Hugues; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the revised selected papers of the Third International Conference on Networked Systems, NETYS 2015, held in Agadir, Morocco, in May 2015. The 29 full papers and 12 short papers presented together with 22 poster abstracts were carefully reviewed and selected from 133 submissions. They address major topics such as multi-core architectures; concurrent and distributed algorithms; middleware environments; storage clusters; social networks; peer-to-peer networks; sensor networks; wireless and mobile networks; and privacy and security measures.
Multi-core architectures -- Concurrent and distributed algorithms -- Middleware environments -- Storage clusters -- Social networks -- Peer-to-peer networks -- Sensor networks -- Wireless and mobile networks -- Privacy and security measures.
Keywords: Computer Communication Networks; Computer software; Software engineering; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Information Systems Applications (incl. Internet).